Clinical correlates of memory complaints during AED treatment. (12th January 2016) - Mula, M.; von Oertzen, T. J.; Cock, H. R.; Lozsadi, D. A.; Agrawal, N.
Abstract : Objectives: To investigate clinical correlates of memory complaints (MC) during anti‐epileptic drug (AEDs) treatment in adults with epilepsy with special attention to the role of depression, using user‐friendly standardized clinical instruments which can be adopted in any outpatient setting. Materials & methods: Data from a consecutive sample of adult outpatients with epilepsy assessed with the Neurological Disorder Depression Inventory for Epilepsy (NDDIE), the Adverse Event Profile (AEP) and the Emotional Thermometer (ET) were analysed. Results: From a total sample of 443 patients, 28.4% reported MC as 'always' a problem. These patients were less likely to be seizure free (18.3% vs 34.3%; P < 0.001), had a high number of previous AED trials (4 vs 3; P < 0.001) and high AEP total scores (49 vs 34.2; P < 0.001). There was no correlation with specific AED type or combination. Depression was the major determinant with a 2‐fold increased risk (95%CI 1.15–3.86; P = 0.016). When depression was already known and under treatment, patients with MC were less likely to be in remission from depression despite antidepressant treatment (11.9% vs 1.6% P < 0.001). Among patients without depression, those reporting MC presented with significantly high scores for depression (3.3 vs 2; t = 3.07; P = 0.003), anxiety (4.5 vs 2.7; t = 4.43; P < 0.001), anger (3 vs 2; t = 2.623; P = 0.009) and distress (3.8 vs 2.2; t = 4.027; P < 0.001) than those without MC. Conclusions: Depression has to be appropriately treated and full remission from depression should represent the ultimate goal as subthreshold or residual mood and anxiety symptoms can contribute to MC.